Direct growth of oriented nanocrystals of gamma-iron on graphene oxide substrates. Detailed analysis of the factors affecting unexpected formation of the gamma-iron phase. (26th July 2019) - Khannanov, Artur; Kiiamov, Airat; Valimukhametova, Alina; Vagizov, Farit G.; Dimiev, Ayrat M.
Abstract : Substrate-oriented nanocrystals of room-temperature-stable gamma-iron have been synthesized by a two-step impregnation/annealing method on a graphene oxide surface. Abstract : In bulk, face-centered gamma-iron exists only at temperatures above 917 °C, returning back to body-centered alpha-iron upon cooling below this temperature. In this work, we report formation of the gamma-iron phase at temperatures significantly lower than the 917 °C threshold in the form of nanoparticles. Moreover, the as-grown nanoparticles have specific orientation along the (002) plane as the result of the templating effect of the graphene oxide substrate. Also, we provide a complete account of the factors responsible for the formation of the gamma-phase. Namely, we demonstrate the role of the type of carbon substrate, and the effect of the temperature and time of annealing and the graphene oxide/iron ion ratio. We demonstrate that the gamma-phase is not formed when using three-dimensional forms of carbon, elucidating the "magic" role of graphene oxide in this process.